Implications of the integral approach to quarterly reporting for the post-earnings-announcement... - Rangan, Srinivasan; Sloan, Richard G. (The Accounting Review, 1998)
We provide evidence that the auto-regressive structure of seasonally differenced quarterly earnings is consistent with the requirements of the integral approach to interim reporting. In particular, we show that the auto-regressive coefficients for standardized seasonally differenced quarterly earnings are larger when the quarters employed in the auto-regressions belong to the same fiscal year than when they belong to different fiscal years. We then show that the signs and magnitudes of abnormal stock returns following earnings announcements are systematically related to these differences in the auto-regressive structure of seasonally differenced quarterly earnings. Specifically, stock returns act as if investors underestimate the larger auto-regressive coefficients between quarters in the same fiscal year. Thus, we corroborate and extend the Bernard and Thomas (1990) hypothesis that stock prices fail to reflect the extent to which quarterly earnings series differ from a seasonal random walk.